Strategi Pengelolaan Persediaan Barang Jadi untuk Meningkatkan Efisiensi Distribusi PT Integriya Dekorindo - Putri Najwa Minadhifah; Ajeng Tita Nawangsari (Universitas Katolik Widya Karya Malang, 2025)
Finished goods inventory management plays a vital role in maintaining production continuity, ensuring customer satisfaction, and supporting overall operational efficiency. PT Integriya Dekorindo, a company engaged in the furniture manufacturing industry, continues to face challenges in aligning production output with fluctuating market demand, minimizing warehouse costs, and ensuring on-time delivery to customers. This study aims to analyze the company’s finished goods inventory management strategies, identify the key obstacles encountered, and provide practical recommendations to enhance distribution effectiveness. Using a qualitative case study approach, data were collected through field observations, document analysis, and the author’s direct practical experience within the company. The findings reveal that the integration of an ERP (SAP) system, demand-driven production planning, and digital-based distribution tracking significantly improve data accuracy, streamline operations, and enable data-driven decision-making. However, persistent issues such as inconsistencies between physical and digital inventory records, risks of overstocking or understocking, and delivery delays still hinder optimal performance. Therefore, adopting an adaptive and collaborative inventory management model supported by digital transformation and continuous monitoring is essential to achieve distribution efficiency and maintain the company’s competitive advantage in the global furniture market.